Does the number of previous miscarriages influence the incidence of chromosomal aberrations in spontaneous pregnancy loss?. (17th December 2017) - Goldstein, Myriam; Svirsky, Ran; Reches, Adi; Yaron, Yuval
Abstract: Objective: Chromosomal aberrations are a common cause for miscarriage. The purpose of this study was to evaluate factors that influence the frequency of chromosomal abnormalities in miscarriages and provide clinicians with a guideline for management of such cases. Methods: The study included 170 women who experienced pregnancy loss between the 2004 and 2014. Cytogenetic analysis of products of conception (POC) was routinely performed. Results: Successful cytogenetic analysis was achieved in 144 cases (84%). Of these, 78 cases (54%) had a chromosomal aberration. The incidence of chromosomal aberrations was not statistically significant among patients with 1, 2, 3, 4 or ≥5 previous miscarriages (33.3%, 57.4%, 48.6%, 65.2%, and 59.1%, respectively, p  = 0.227). The F/M ratio was similar in normal and abnormal POC karyotypes (1.2:1 and 1.3:1, respectively, p  = 0.7). Conclusion: Contrary to previous assumptions we did not find correlation between number of previous spontaneous miscarriages a women experienced and chromosomal aberration in her current miscarriage.